Proposals and resources for suicide prevention in high schools (Revista Estudios Psicológicos, 2022)
Suicide is a multidimensional phenomenon and is the second leading cause of death for young people. The objective was to identify the suicidal risk, determinants, and prevention strategies in secondary schools from the perception of their health staff. To achieve this, a mixed methodology was followed based on a questionnaire with questions on a Likert scale and open questions analyzed through axial coding and with the theory of cultural consensus. Health personnel from 159 schools in the city of León, Guanajuato, Mexico were surveyed. It is noteworthy that in public schools there is a higher risk of suicide and more related to family violence, and in private schools, it is associated with drug use. The leading resource to address the risk is the health or teaching staff. The proposals were focused on or indicated with the support of external institutions. There was little consensus on the proposals, representing a high cultural capital. Knowing the vision of those responsible for students’ health can generate new ideas to prevent suicide in students.
Keywords: cultural consensus; prevention; students; suicide; teachers